EXPERIENCES DAN NEED FOR UNIQUENESS MEMOTIVASI PELANGGAN COFFEE SHOP AREA JABODETABEK DALAM MELAKUKAN SWOM. - Fauzi, Fani Ahmad; Kurniawati, Kurniawati; Kurniawan, Andri; Kartika, Devi; Florensia, Florensia; Soefhwan, Soefhwan (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2022)
This study is conducted with the aims of assessing the effect of Experiences, Reflection of Self, Need for Uniqueness on the contribution of sWOM mediated by Opinion Leadership in coffee shops in the Greater Jakarta area. The sampling procedure used to collect relevant data was using a questionnaire. The study was conducted on 190 respondents as purposive sampling. Data analysis using SEM (structural equation modeling) and Analysis of Moment Structure (AMOS) software. The results of data analysis showed that opinion leadership factors and need for uniqueness positively affected on the contribution of sWOM, while experience and self-reflection had a positive effect on the contribution of sWOM if through opinion leadership mediation. The findings of this study provide advice to coffee shop’s entrepreneurs in Jabodetabek to pay more attention to elements such as places, services and products that can provide different experiences for consumers, unique, and in accordance with the image of consumers who are targeted, so that they can motivate customers to do sWOM. On the other hand, it is also recommended to optimize the role of opinion leaders in social media to promote through their influence in the digital world.